Предмет:
МатематикаАвтор:
аноним1)
(а - 3)(а - 5) и (а - 4)^2;
(a - 3) * (a - 5) = a^2 - 5a - 3a + 15 = a^2 - 8a + 15;
(a^2 - 8a + 15) - (a - 4)^2 = a^2 - 8a + 15 - a^2 + 8a - 16 = -1;
-1 < 0 => (a - 4)^2 > (а - 3)(а - 5);
2) а) а - b = -0,001;
-0,001 < 0 => b > a;
б) a - b = 0;
a = b.
Пояснение: Если одно число больше другого, то разность между ними будет отрицательной.
Автор:
daniela66Добавить свой ответ
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть